Eksistensi Dayah di Tengah Modernisasi: Sejarah, Kurikulum, dan Transformasi Pendidikan Islam di Aceh - Mohammad Aquallurrizal; Beta Hikmah Zahrotunnisa; Nisa Nur Fadilah; Sutrimo Purnomo (Jurnal Bintang Pendidikan Indonesia, 2026)
This study aims to examine the existence of dayah as a traditional Islamic educational institution in Aceh in facing the challenges of modernization, as well as to analyze its history, curriculum, and the dynamics of educational transformation within it. This research employs a qualitative approach through library research by collecting data from various sources such as books, scientific journals, research articles, and documents relevant to the topic. The findings indicate that dayah is one of the oldest Islamic educational institutions in Aceh that developed since the early spread of Islam in the Indonesian archipelago and has played an important role in the dissemination of Islamic teachings, moral development, and the formation of social life within the community. The educational system in dayah focuses on the study of classical Islamic texts (kitab kuning) and Islamic sciences through traditional learning methods such as halaqah, religious book studies, and direct learning with teungku or Islamic scholars. Over time, dayah institutions have undergone various transformations through the integration of general subjects, curriculum reform, and improvements in educational management systems in order to remain relevant to modern societal needs. Modernization presents challenges for dayah, particularly in maintaining a balance between tradition and educational innovation. Nevertheless, dayah continues to preserve its Islamic identity while gradually adapting to contemporary developments. Therefore, dayah not only survives as a traditional educational institution but also develops into an adaptive and relevant Islamic educational institution that continues to play a significant role in shaping character and religious values in Acehnese society.